ANALISIS EFEKTIVITAS PENGGUNAAN TOKOH AGAMA DALAM PEMBENTUKAN CITRA PRODUK PERUSAHAAN - Santika, Dewi (MABIS, 2012)
This research was conducted to know the effectivity of using religious figure as a brand ambassador in form a good image for the product. This research used descriptive research and the research methods were survey method. The factors in this research which influence the product image were grouped into product acknowledge, religious figure acknowledge, efficiency of using religious figure, the advertising contents can confidence the audiens, and the product image can be representative by religious figure. Data collection techniques used was interview, questioner, and bibliography study. Sampling method was judgemental sampling with the respondents are those who buy more then 5 botol and for their own consumption. Data analysis technique used in this research was qualitative analysis technique.Â Â